Quantitative and comprehensive analysis of Ciona notochord organogenesis - Winkley, Konner Michael (Kansas State University, 2020)
Technical advances in imaging and genomics are making developmental biology increasingly quantitative. The invertebrate chordate Ciona has small embryos, a compact genome, and a simple, yet stereotypically chordate body plan, making it well suited to quantitative, systems-level studies of organogenesis. This is particularly true for the Ciona notochord, which is comprised of only 40 cells that form a simple tapered rod. The unifying theme of this dissertation is to comprehensively and quantitatively analyze the development of the Ciona notochord in terms of both the cell behaviors driving morphogenesis and the gene regulatory networks controlling notochord cell fate. Ciona embryos develop rapidly, and, since they are poikilotherms, at a rate proportional to the temperature at which they are incubated. I required precise embryonic staging of the temporally dynamic transcriptional and morphogenetic processes I was studying in order to make accurate conclusions. To facilitate this, we developed a simple yet powerful open source device, the Temperature Adjusted Developmental Timer, which allows researchers to stage embryos accurately with respect to temperature in real time and requires only the estimation of two simple species-specific parameters. Using quantitative confocal microscopy and computational image analysis, I quantified how a series of subtle but iterative asymmetric divisions give rise to the observed cell volume differences along the AP axis of the post-mitotic notochord which contributes to its tapered shape. I partitioned the contributions of three cellular mechanisms to the observed asymmetric divisions using a modeling framework and uncovered a previously unappreciated role of mother-cell shape in this process. To characterize the earliest gene-regulatory network (GRN) of the notochord, I collected a single-cell RNA-sequencing (scRNAseq) timecourse of early Ciona development during the stages in which notochord and many other distinct cell fates are established. This was performed both with and without a pharmacological inhibitor of a MAPK-dependent signal involved in many early cell fate decisions including notochord. The scRNAseq data revealed that the earliest signatures of the Ciona notochord GRN involve transcriptional activation by Ets and Zic family transcription factors in parallel to, and not downstream of the notochord specific transcription factor Brachyury. These diverse studies of notochord organogenesis are linked in being deeply quantitative and based on assessing cellular properties and behaviors with single-cell resolution on a scale ranging from an entire organ primordium to an entire embryo. Both the asymmetric division study and the scRNAseq study have broad implications beyond the Ciona notochord and contribute to a modern understanding of the processes of development at the single-cell level.
Keywords: Ciona; Cell fate; Differentiation; Asymmetric division; Single-cell RNAseq; Developmental biology